The anthropic principle and the programmatic assumptions of recentivism - Szczupak, Krzysztof (Folia Philosophica, 2001)
The article presents the most important ideas of the anthropic principle on the background of the Józef Banka’s philosophy of recentivism. The anthropic principle evokes numerous discussions and controversies both in sciences and in philosophy. It is a manifestation of “anthropologisation” of the contemporary science, though of “anthropologisation” perceived differently than it is understood by philosophers. Instead of the notion of “cognising sub ject” the anthropic principle makes use of the notion of “observer” who or which can be a man an extraterritorial reasonable creature, or a quantum computer.